Huella de Carbono de la carne: Un estudio de caso - Bongiovanni, Rodolfo (2023)
Carbon footprint of beef: A case study Abstract. The aim of this study was to analyze the carbon footprint of beef production, with field rearing and rearing plus fattening in a feedlot, in a circular economy system, in the southeast of San Luis, Argentina, for three categories of animals: male TBeef (up to 503 kg), female TBeef (up to 502 kg) and Gombu (up to 606 kg). The functional unit is 1 kg of boneless frozen beef, red Aberdeen Angus breed, packed and placed in the export port. Breeding takes place in natural and implanted pastures. Weaning was performed at 6 months of age (150 kg for females and 185 kg for males). Rearing was carried out in a corral and lasted 105 days for males (up to 299 kg) and 135 days for females (up to 305 kg). Fattening was carried out in a feedlot and lasted 180 days for TBeef males, 210 days for TBeef females and 285 days for Gombu. The carbon footprint was 21.6 kgCO2eq for male TBeef, 24.0 kgCO2eq for female TBeef, and 20.3 kgCO2eq for Gombu. The hotspot was enteric fermentation, representing tween 63 % and 65 % of the total impact. The female TBeef had the largest footprint because it required more rearing and fattening days to reach the same sales weight as the male Tbeef. This implies the greatest use of resources and more days of emissions from enteric fermentation and manure management. The category with the lowest emissions was Gombu, since it was fattened up to the final 606 kg, so the total impact of its production was divided into a higher final weight. The results are considerably below the surveyed bibliography, which is explained by the integrated circular economy system. A high percentage of the diet was byproducts of ethanol production because they used the effluents for a biodigester and because nitrogenous fertilisers were reduced.